Wild Profusions: An Ode to Academic Hair - McLarnon, Mitchell; Leggo, Carl; Sinner, Anita (Journal of the Canadian Association for Curriculum Studies, 2018)
With the intention of expanding educational conversations through playful encounters, we braid curricular intensities inspired by wild profusions, written in our academic hair and offered as expressions of life writing. Through our hairatives, we share discomforts and provocations that are the stories of our scholarly identities, rooted in the body-word nexus as affective attunements. Through our entanglements, we map our networks of relations and invite curricular conductivity concerning how and why hair is formative in the context of the academy. Living on the precarious margins of stories, we share our narratives within the folds of educational theory to passionately and poetically render our richly textured events as the moments of knowledge creation. In this way, our hair serves as an artistic configuration, where we are manifest in “situated inquiry about the truth that it locally actualises”, to borrow from Badiou (2005), opening what may be described as an “eventual rupture” of our scholarly truths (p. 12). Our ruminations are the imaginaries of academics, or simply living intensities. We intend to crack open from the inside that which is “a reality concealed behind appearances” in an attempt to reconfigure “a different regime of perception and signification” (Rancière, 2009, pp. 48, 49).